SURGICAL ISSUES OF SEGMENTAL MANDIBULAR RESECTION IN THE COMBINATION AND COMPLEX TREATMENT OF LOCALLY ADVANCED AND RECURRENT OROPHARYNGEAL CANCER - D. V. Sikorsky; S. O. Podvyaznikov; A. N. Volodin; A. A. Chernyavsky (Опухоли головы и шеи, 2015)
Segmental mandibular resection is frequently a mandatory component of combination surgery in the treatment of locally advanced and recurrent oropharyngeal cancer.Objective: to detail the specific features of segmental mandibular resection, as applied to combination and complex treatment of locally advanced and recurrent oropharyngeal cancer. This study was based on the clinical observations of 31 patients with locally advanced and recurrent oropharyngeal cancer, who had been operated on in Cancer Surgery Unit One, Nizhny Regional Oncology Dispensary, Branch One (Nizhny Novgorod Oncology Dispensary before 2010), in the period 2005 to 2011.Results. Postoperative complications developed in 16 (50 %) patients: mild, moderate, and severe complications in 2, 8, and 6 patients, respectively. Thirteen patients were alive more than 2 years after surgery. Among in the deceased (n = 18), the cause of death was primary tumor progression in 10 patients; lung metastases developed in 1 patient; a second primary tumor (central lung cancer) did in 1 case. In the immediate postoperative period, two patients died (from gastric bleedingand pulmonary thromboembolism). In 4 dead patients, the causes of death were unassociated with a tumor process, but were associated with cardiovascular diseases.Conclusion. Segmental mandibular resection techniques during surgery are responsible for not only the frequency of postoperative complications, but also primarily for the efficiency of performed surgical treatment.